Butterflies of Renuka Wildlife Sanctuary, Sirmaur District, Himachal Pradesh, India - Singh, Arun P. (Indian Forester, 2008)
Two sampling surveys during November 2007 and June 2008 in Renuka Wildlife Sanctuary and adjacent areas, located in the West Himalayan foothills, revealed the occurrence of 118 species of butterflies. Amongst these were seven protected species under the Indian Wildlife (Protection) Act, 1972 including some rarities like the Brown Onyx, H. viola, Gaudy Baron, Euthalia lubentina; Great Swift, Peliopidas assamensis and Large-banded Swift, P. sinensis. Besides, 12 species from adjoining 'temperate' forests migrated down during winter to this 'deciduous' habitat. Species similarity of Renuka Wildlife Sanctuary was determined to be more similar to New Forest, Dehra Dun located at the base of the Himalayan foothills than Simbalbara Wildlife Sanctuary located nearby on the Shiwalik ranges. High point diversity and presence of rare species of conservation priority all make this Sanctuary a unique habitat in the region.